2009
DOI: 10.1007/s10661-009-0761-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological indoor air quality in an Italian office building equipped with an HVAC system

Abstract: The purpose of this study was to evaluate the level and composition of bacteria and fungi in the indoor air of an Italian office building equipped with a heating, ventilation and air conditioning (HVAC) system. Airborne bacteria and fungi were collected in three open-space offices during different seasons. The microbial levels in the outdoor air, supply air diffusers, fan coil air flow and air treatment unit humidification water tank were used to evaluate the influence of the HVAC system on indoor air quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 31 publications
6
72
0
2
Order By: Relevance
“…The quality of indoor air can be affected by various factors, such as inappropriate selection of indoor materials or heating, ventilation, and air conditioning (HVAC) systems (based on their excessive CO 2 concentrations). This can provide a hospitable environment for growing airborne bacteria and fungi, and subsequently, results in increasing the possibility for respiratory diseases, namely asthma (Bonetta et al 2010). Poor quality of indoor air can directly influence the residents' health and their performances (Pegas et al 2011).…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…The quality of indoor air can be affected by various factors, such as inappropriate selection of indoor materials or heating, ventilation, and air conditioning (HVAC) systems (based on their excessive CO 2 concentrations). This can provide a hospitable environment for growing airborne bacteria and fungi, and subsequently, results in increasing the possibility for respiratory diseases, namely asthma (Bonetta et al 2010). Poor quality of indoor air can directly influence the residents' health and their performances (Pegas et al 2011).…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…In this study, among the bacterial genera, Bacillus, Micrococcus and Staphylococcus were most abundant and among the fungal genera, Aspergillus and Penicillium were most abundant. Brandal et al (2014) reported that Bacillus and Staphylococcus are the most frequent in airborne microflora whereas Bonetta et al (2010) found Staphylococcus and Micrococcus as the most common bacterial genera in indoor air.…”
Section: Fig 1 Map Showing Outdoor (Od) and Indoor (Id) Sample Collmentioning
confidence: 99%
“…2,3 The culturable fraction of indoor microorganisms has been relatively welldocumented. [4][5][6] However, the majority of publications have focused on molds and their spores, and there is comparatively little information on bacteria in the indoor climate. The bacteria most often found in indoor environments such as schools and nurseries are grampositive genera such as Micrococcus and Staphylococcus.…”
Section: Introductionmentioning
confidence: 99%